Music Therapy for Patients Who Have Undergone Hematopoietic Stem Cell Transplant. (9th January 2014) - Ratcliff, Chelsea G.; Prinsloo, Sarah; Richardson, Michael; Baynham-Fletcher, Laura; Lee, Richard; Chaoul, Alejandro; Cohen, Marlene Z.; de Lima, Marcos; Cohen, Lorenzo
Abstract : Objectives . This study examines the short- and long-term QOL benefits of a music therapy intervention for patients recovering from hematopoietic stem cell transplantation (HSCT). Methods . Ninety allogeneic HSCT patients, after transplant, were randomized to receive ISO-principle (i.e., mood matching) based music therapy (MT; n = 29 ), unstructured music (UM; n = 30 ), or usual care (UC; n = 31 ) for four weeks. The ISO principle posits that patients may shift their mood from one state to another by listening to music that is "equal to" the individual's initial mood state and subsequently listening to music selections that gradually shift in tempo and mood to match the patient's desired disposition. Participants in MT and UM groups developed two audio CDs to help them feel more relaxed and energized and were instructed to use the CDs to improve their mood as needed. Short-term effects on mood and long-term effects on QOL were examined. Results . MT and UM participants reported improved mood immediately after listening to CDs; the within-group effect was greater for UM participants compared to MT participants. Participant group was not associated with long-term QOL outcomes. Conclusions . Music listening improves mood acutely but was not associated with long-term benefits in this study.